Transition, abstraction and perverse concreteness in J.G. Ballard's High-Rise. Issue Volume 32:Issue10(2018) (26th November 2018) - Davies, Jonathan
ABSTRACT: This article examines Ballard's High-Rise (1975) as a novel of transition, mediating wider political-economic, architectural and libidinal reconfigurations in 1970s Britain, with a particular focus on its class politics and navigation of the abstract/concrete dichotomy. In tracing the inspiration behind Ballard's fictional residential complex, the article situates High-Rise with respect to proximate debates around high modernist and anti- or post-modernist architectural paradigms, showing how Ballard dramatises certain positions and anticipates others. It then focuses on Ballard's imagined revolt, exploring how the novel aligns two purificatory designations of the 'real' – a 'real architecture' stripped of adornment and a 'real' perverse or primitive desiring-subject stripped of socialised prohibitions. This revolt, I argue, is comprehensible as a particular assault on abstraction, as characters retreat from the realm of labour and commodity exchange, from the building's instrumental design features, in pursuit of a new immediacy at the level of desire, a perverse 'concreteness'. The article also invokes two theoretical texts that are roughly contemporaneous with High-Rise, namely Deleuze and Guattari's Anti-Oedipus (1972) and Lefebvre's The Production of Space (1974), to assess the broader social dynamics of this perverse revolt and the fetishised apprehensions of social space that emerge as a corollary.